A dual-based algorithm for solving lexicographic multiple objective programs - Pourkarimi, L.; Zarepisheh, M. (European journal of operational research, 2007)
In this paper, we propose an algorithm for solving lexicographic multiple objective programs based upon duality theorem. In the existing algorithm, we should solve several linear programming problems (LPPs); therefore if, in particular, there are several objective functions, this method is not worthwhile from the viewpoint of computation. But in our new algorithm we just solve one LPP.